2022
DOI: 10.1093/nar/gkac1079
|View full text |Cite
|
Sign up to set email alerts
|

Origins of transfer establish networks of functional dependencies for plasmid transfer by conjugation

Abstract: Plasmids can be transferred between cells by conjugation, thereby driving bacterial evolution by horizontal gene transfer. Yet, we ignore the molecular mechanisms of transfer for many plasmids because they lack all protein-coding genes required for conjugation. We solved this conundrum by identifying hundreds of plasmids and chromosomes with conjugative origins of transfer in Escherichia coli and Staphylococcus aureus. These plasmids (pOriT) hijack the relaxases of conjugative or mobilizable elements, but not … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 66 publications
(88 reference statements)
0
39
0
Order By: Relevance
“…The consistency in size distribution for most subgenomic sized ACCs across samples could either be due to a particular set of selectively advantageous genes, or even type of plasmid mobility. Previous studies that have also observed bi-modal distribution of plasmids within species observed correlations between mobility type and plasmid sizes (12). Additionally, it is possible that size constraints can result from bacteriophage transduction of plasmids which are limited by size compatibility -and similar to the observation of bacteriophage and plasmid size distributions made in the study by (12).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The consistency in size distribution for most subgenomic sized ACCs across samples could either be due to a particular set of selectively advantageous genes, or even type of plasmid mobility. Previous studies that have also observed bi-modal distribution of plasmids within species observed correlations between mobility type and plasmid sizes (12). Additionally, it is possible that size constraints can result from bacteriophage transduction of plasmids which are limited by size compatibility -and similar to the observation of bacteriophage and plasmid size distributions made in the study by (12).…”
Section: Resultsmentioning
confidence: 60%
“…Previous studies that have also observed bi-modal distribution of plasmids within species observed correlations between mobility type and plasmid sizes (12). Additionally, it is possible that size constraints can result from bacteriophage transduction of plasmids which are limited by size compatibility -and similar to the observation of bacteriophage and plasmid size distributions made in the study by (12). Interestingly, the largest peak in our putative bacteriophage ACCs matches the largest of the two peaks observed for all ACCs at approximately 42 kbp.…”
Section: Resultsmentioning
confidence: 84%
“…These will allow studying additional plasmids and specifically investigating early expressed genes in small plasmids encoding only an oriT . Such small plasmids are important to study, as they have been shown to carry numerous antimicrobial resistance genes (ARGs) and make up at least half of all plasmids 5,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses were restricted to conjugative elements with a relaxase and a known oriT sequence, which were required to determine the transfer directionality. However, a large portion of the relaxase-containing sequences lacked a known oriT sequence, hampering our ability to comprehensively study potential conjugative elements 8,12 . Further, numerous small plasmids do not encode for relaxases and undergo transfer by exploiting the relaxosome of other conjugative elements in trans 85,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation